Capitalization of BRT Network Expansions Effects into Prices of Non-expansion Areas - Rodriguez, Daniel A.; Mojica, Carlos H. (2012)
A before and after hedonic model is used to determine the property value impacts on properties already served by the transit system caused by extensions to Bogota's bus rapid transit system. Asking prices of residential properties belonging to an intervention area (N = 1,407 before, 1,570 after) or a control area (N = 267 before, 732 after) and offered for sale between 2001 and 2006 are used to determine capitalization of the enhanced regional access provided by the extension. Properties offered during the year the extension was inaugurated and in subsequent years have asking prices that are between 13% and 14% higher than prices for properties in the control area, after adjusting for structural, neighborhood, and regional accessibility characteristics of each property. Furthermore, the appreciation is similar for properties within 500 m and properties between 500 m and 1km of the BRT.